The Effect of Extract (Angelica Keiskei) on Reducing Blood Pressure Level among Post-Partum Period with Hypertension - Sania Lailatul Rahmi; Supriyana Supriyana; Apoina Kartini (Alta Dharma Publisher, 2020)
A third of women who experience pregnancy hypertension or pre-eclampsia will continue in the postpartum period and reach their peak on days 3-6 postpartum. The study aimed to examine Ashitaba extract (Angelica keiskei) on reducing blood pressure levels among hypertensive postpartum. A quasi-experimental study design, pre-test, and post-test with the non-equivalent control group were applied in this study. Thirty samples were selected and divided into the experimental group and the control group. The experimental group received the Ashitaba extract, and the control group received nifedipine. The findings showed that systolic blood pressure among the intervention group was significantly decreased than the control group. This study proved the effective Ashitaba extract as an alternative therapy to reduce blood pressure among postpartum hypertensive mothers